Investigating the Role of Trust in Virtual Team Management: A Qualitative Inquiry - Ngadi Permana; Eri Kusnanto; Yessica Amelia (LPPM STIE Kasih Bangsa, 2024)
This qualitative study delves into the crucial role of trust in the management of virtual teams. The research aims to investigate how trust influences the dynamics of virtual team functioning. Employing a qualitative approach, this study utilizes semi-structured interviews with virtual team managers and members to gather rich insights into their experiences and perspectives. Data analysis involves thematic analysis, identifying recurring patterns and themes related to trust in virtual team environments. The findings underscore the significance of trust in fostering effective communication, collaboration, and performance within virtual teams. Moreover, the study illuminates the nuances of trust-building strategies and challenges faced in virtual team settings. This research contributes to a deeper understanding of the complexities of managing virtual teams and offers valuable insights for practitioners and scholars alike.